Characterisation of Ground Coffee Waste-based Biocomposite - Tan, Ming Yee (UNIMAS, 2017)
The escalating awareness for the need of greener and sustainable technologies has resulted in the interest of development of bio-composites. In this study, characterisation of oxo iodegradable high density polyethylene (oxo-HDPE) and ground coffee waste (GCW) biocomposite had been performed. The composites were fabricated using the GCW reinforced HDPE film followed by a hot compression moulding. Fourier transform infrared spectroscopy (FTIR) spectrum indicated the eradication of lipids, hemicellulose, lignin and impurities from GCW particles after the treatments. Thermogravimetric analysis (TGA) executed improved thermal stability while differential scanning calorimetry (DSC) showed increment in degree of crystallinity for all the treated GCW composites. Water absorption demonstrated the treatments had enhanced the hydrophobicity of the treated GCW composites. Scanning electron microscopy (SEM) revealed a coarser surface for the treated GCW as impurities were removed. Besides that, treated composites gave a better GCW/matrix interface. Tensile and impact properties improved after the treatments as a result of better adhesion between filler/matrix. Specific tensile properties improved further as the composites were lighter in weight and density.